The Role of the Kamsel Unit Through Dikmas Lantas in Efforts to Reduce the Number of Traffic Violations by Underage Motorists in the Jurisdiction of Tulungagung Police - Alfarisi, Davis (Advances in Police Science Research Journal, 2024)
This research is motivated by the increasing number of motorist traffic violations in minors in Tulungagung Regency. The South Kalimantan Unit plays a role in pre-emptive functions educate the public about traffic, in order to minimize the occurrence of traffic violations under age. However, the community education that has been carried out has not shown maximum results. marked by an increase in the number of traffic violations from 2021 to 2023. This research uses a qualitative approach by collecting data through observations, interviews, and document studies. The research instruments used are guided by Management Theory, Communication Theory, Cooperation Theory, SWOT Theory, Role Concept, Community Education Concept Then, and the Concept of Past Violations. Then, put it in the form of questions interview. The results of this research show that the implementation of community service is carried out by the Traffic Security Unit Tulungagung Police are not yet optimal even though they have tried to reduce traffic violations, especially among teenagers. This activity is supported by a clear legal basis, DIPA budget, and human resources competent, but hampered by a lack of personnel and facilities and infrastructure. this unit using varied methods in implementation and supervision, including performance evaluation, budget monitoring, and community response. There are opportunities to utilize social media and cooperation with related parties, while the challenge is in the form of a black spot in the Tulungagung location as industrial area. The role of the South Kalimantan Unit is not only as a law enforcer but also to promote it socialization and education to prevent violations, with cooperation and use of technology as part of their strategy.